Pembuatan papan blockboard menggunakan limbah batang kelapa sawit sebagai upaya pelestarian lingkungan - Romiyadi, Romiyadi; Frinaldi, Aldri; Lanin, Dasman; Rembrandt, Rembrandt (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study was conducted to make blockboard using oil palm trunk waste as raw material. The purpose of this study was to determine the physical and mechanical properties of blockboard made from oil palm trunk raw materials and compared with the physical and mechanical properties of blockboard available on the market. The mechanical properties tested were tensile strength, flexural strength and air absorption. The oil palm trunk used was waste from rejuvenation that was 25-30 years old. The results showed that blockboard made from oil palm trunk waste had higher tensile strength and flexural strength values ??than market blockboard. Meanwhile, the water absorption capacity of market blockboard is better than the water absorption capacity of blockboard made from oil palm trunk waste. This study was conducted to implement one of the government policies in the context of utilizing oil palm waste, especially oil palm trunk waste as an effort to preserve the environment.